Handbook of polymer coatings for electronics : chemistry, technology and applications - Licari, James J., 1930- (Noyes Publications, 1990)
Covers the theoretical aspects of coatings (molecular structure of polymer types and their correlation with electrical and physical properties) and applied aspects (functions, deposition processes, applications, testing). Over 100 proprietary coating formulations were reviewed, their properties collated, and tables of comparative properties prepared. Serves as both a primer and as a handbook for collecting properties data.
Keywords: Electronic packaging -- Materials.; Polymers.; elektronické knihy; electronic books